A68 COST EFFECTIVENESS OF TIGHT CONTROL FOR CROHN'S DISEASE WITH ADALIMUMAB-BASED TREATMENT: ECONOMIC EVALUATION OF CALM TRIAL FROM CANADIAN PERSPECTIVE. (15th March 2019) - Panaccione, R; Colombel, J; Bossuyt, P; Baert, F; Vanasek, T; Danalioglu, A; Novacek, G; Armuzzi, A; Reinisch, W; Johnson, S; Buessing, M; Neimark, E; et al.
Abstract: Background: Tight control (TC) for Crohn's disease (CD), using symptoms plus biomarkers (faecal calprotectin, C-reactive protein) to direct adalimumab (ADA) treatment, was associated with improved outcomes and considered cost effective (from United Kingdom setting) compared to clinical management (CM) in a 48-week (wk) multicenter, randomized controlled trial (CALM). Aims: This study aims to evaluate the cost-effectiveness (CE) of TC vs CM from Canadian perspective. Methods: The CE of TC versus CM was assessed in a Canadian setting. An ordered probit regression estimated CDAI-based health state (remission: CDAI <150, moderate: CDAI ≥150 to <300, severe: CDAI ≥300 to <450, very severe: CDAI ≥450) transition matrices for TC and CM pts; the matrices predicted pt health states weekly over 5 years (yrs). A probit predicted likelihood of hospitalization as a function of health state and randomization to TC or CM. Observed ADA 40mg injections were summed over 48 wk, average injections over wk 23 to 48 were assumed to continue from wk 49 to 260. ADA costs (in Can) were based on Ontario list price. Health states were associated with health utility and costs related to other direct medical services. Remission rate, CD-related hospitalizations, ADA injections, other direct medical costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were calculated at 2 and 5 yrs. Work Productivity and Activity Impairment was converted into productivity measures using Canadian average weekly earnings, and probabilistic sensitivity analyses (PSA) were conducted. Results: Over 2 yrs, TC was associated with a higher remission rate (65.3% vs 50.7%), fewer CD-related hospitalizations (0.275 vs 0.720/person yr) and more ADA injections (mean 61.34 vs 46.17) than CM. Total medical costs over 2 yrs were 54, 359 and 49, 939 for TC and CM; TC had 0.09 higher QALYs (95% confidence interval [CI]: 0.16 to 0.03) and 4, 420 higher total medical costs (95% CI: 2, 096 to -12, 952). The ICER was 51, 150 per QALY (95% CI: 135, 451 to -405, 049). PSA simulations indicated 77.2% of the time an ICER was below a cost-per-QALY threshold of 50, 000. TC became dominant (i.e., ICER<0) when including the costs associated with work productivity gained (-16, 103 in TC and -10, 713 in CM). The results for 5-yr timeframe were similar, with an ICER of 48, 066 in base case and a negative ICER when including work productivity costs. Conclusions: CE of TC improved over time when extrapolating outcomes from CALM in the Canadian setting. Incorporating costs related to work productivity further strengthened the economic value of TC. Funding Agencies: None